The Effect of Music Therapy on Declining Anxiety of Cancer Patients Undergoing Chemotherapy: Literature Review - Mahardhika Rahmawati, Primasari; Abdillah, Achlish; Siska Ravinawati , Devin (Universitas Bondowoso, 2023)
Introduction: Chronic disease in the presence of abnormal cells that grow faster than the normal limits of cells in general with the most commonly used medical treatment being chemotherapy. Chemotherapy treatment has several side effects, one of which is anxiety. However, there is one non-pharmacological therapy that can be applied to reduce the feeling of anxiety, namely music therapy. The purpose of writing this literature review is to identify the effectiveness of music therapy against decreased anxiety in cancer patients undergoing chemotherapy. Method: The method used in writing is a literature review in the form of a literature review obtained from the PubMed, Google Scholar and Springerlink databases. After going through the selection stage using the Critical Appraisal Joanna Briggs Institute (JBI), 11 journals were obtained, 7 of which used randomized control and 4 journals used trial quasy experimental studie. Result: The results of the literature review showed that music therapy to reduce anxiety while undergoing chemotherapy uses various types of duration, namely most of them do music therapy as much as 30 minutes per session, done 2-3 times a week and carried out for 64 weeks. The average instrument used is the State Trait Anxiety Inventory with an assessment of 5.4 - 24.58 Conclusion: From the results of the literature review, it is hoped that nurses and families can apply music therapy interventions to cancer patients undergoing chemotherapy.